Estimates of genetic parameters and cluster analyses for carcass and meat quality traits in birds - Bainy, Adriane Molardi [UNESP]; Savegnago, Rodrigo Pelicioni [UNESP]; Freitas, Luara Afonso de [UNESP]; Nunes, Beatriz do Nascimento [UNESP]; Rosa, Jaqueline Oliveira [UNESP]; Ledur, Monica Correa; Munari, Danisio Prado [UNESP] (Empresa Brasil Pesq Agropec, 2017)
The objective of this work was to estimate genetic parameters for bird carcass and meat quality traits, as well as to explore the genetic patterns of the breeding values of this population using cluster analyses. Data from 1,846 birds were used to estimate the genetic parameters of production and quality traits using the multiple-trait animal model, and cluster analyses were performed. The heritability estimates ranged from 0.08 +/- 0.03 for meat pH measured 24 hours after slaughter to 0.85 +/- 0.09 for body weight. The genetic correlations between production traits were high and positive. The genetic correlations between meat quality traits were low and were not informative due to the high standard errors (same magnitudes as those of the genetic correlations). The genetic correlations between meat production and quality traits were negative, except between production traits and meat lightness intensity. Based on breeding values (EBVs), the evaluated population can be divided into four groups through cluster analyses, and one group is suitable for selection because the birds presented EBVs above and around the average of the population, respectively, for production and quality traits. Therefore, it is possible to obtain genetic gains for production-related traits without decreasing meat quality.
Keywords: genetic correlation; heritability; meat color; White Leghorn